Estimating the relative efficiency of Brazilian publicly and privately owned water utilities: a stochastic cost frontier approach - Souza, Geraldo da Silva e (2016)
Made available in DSpace on 2016-10-10T03:51:48Z (GMT). No. of bitstreams: 2 Estimating the Relative Efficiency of Brazilian Publicly and Privately Owned Water Utilities_A Stochastic Cost Frontier Approach.pdf: 177038 bytes, checksum: 8622714df841213f147be8a7521c0adf (MD5) license.txt: 1818 bytes, checksum: 46de3043f08e87659ae535ef74b8ce9d (MD5) Previous issue date: 2007-08